DESAIN PENGEMBANGAN KURIKULUM PAI SD 44 KOTA BENGKULU - Bogi krisnajaya; Desy Eka Citra Dewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Curriculum development is the next stage in the coaching process which aims to design a new curriculum. The Islamic education curriculum must be consistent with the principles and objectives that have been established. The curriculum is structured as a structure that organizes and arranges its main elements, namely learning materials. This research applies a qualitative approach to understand the subject's experiences using descriptive methods. The participants in this research consisted of school principals and Islamic Religious Education (PAI) teachers. This research aims to evaluate the PAI curriculum design at the elementary school level. In its implementation, the development of the PAI curriculum at SDN 44 experienced a paradigm shift. This curriculum is designed taking into account students' needs, interests and talents, as well as considering their psychological aspects. Therefore, the PAI curriculum must be designed effectively to facilitate the student learning process.